Pertanggung Jawaban Pidana Penghimpunan Dana Masyarakat Tanpa Izin melalui Arisan Online: Analisis Putusan No.119/Pid.Sus/2017/Pn.Tanjung Pandan - Muhammad Tezar Emiral; Madiasa Ablisar; Sunarmi; Mahmud Mulyadi (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the criminal act of collecting public funds without a permit through online arisan (social savings and credit) in Decision Number 119/Pid.Sus/2017/PN Tdn. The issues examined are the qualifications of the crime and the judge's considerations in issuing the verdict. The study uses a normative juridical method with a statutory and case-based approach. The results show that the defendant's actions fulfill all elements of the crime of collecting funds without a permit, so that an 11-year prison sentence and a fine of IDR 10 billion are appropriate. It is recommended that supervision of illegal online arisan be increased and that the public verify the legality of organizers before participating.